Transforming audience experience to design enjoyable exhibition - Wang, Nan (2018)
Exhibition is a natural and intrinsic human behaviour for communication; with the coming of the information society and the experience economy, exhibition design has been considered as an effective tool to achieve the target of cultural engagement and economic benefit. This thesis aims to investigate the relationship among exhibition design factors (EDFs), audience experience factors (AEFs) and behaviour data (BD). It uses mixed method to obtain and analyze multi-data, finding and establishing a framework of designing an enjoyable exhibition (FDEE) (Chapter 5).